Technological Pedagogical and Content Knowledge (TPACK) Based Learning to Improve Student Learning Achievement at SDN Pekojan 03 and SDN Pekojan 05 Tambora, West Jakarta - Jujur Purba; Waska Warta (Eduvest - Journal of Universal Studies, 2026)
Technological Pedagogical and Content Knowledge (TPACK)-based learning is a strategic agenda for improving the quality of education in primary schools. Teachers, as the main implementers of instruction, require systematic management support to effectively integrate technology, pedagogy, and content. This study aims to describe the management of TPACK-based learning through the POAC (Planning, Organizing, Actuating, Controlling) framework in enhancing student achievement at SDN Pekojan 03 and SDN Pekojan 05 Jakarta Barat. The research employed a qualitative approach with a case study design through observations, interviews, and document analysis involving principals, teachers, and students. The findings reveal that planning for TPACK-based learning has been incorporated into instructional documents, yet its implementation remains inconsistent; organizing is still simple with limited ICT management teams; actuating involves the use of digital applications and interactive media, though not evenly across all classrooms; and controlling tends to focus more on administrative compliance rather than in-depth reflection on TPACK effectiveness. Limited facilities, teachers’ digital literacy, and unstable internet connectivity emerge as the main challenges, although both principals and teachers demonstrate strong commitment to sustaining digital learning innovation. The study concludes that applying POAC in TPACK-based learning has the potential to enhance teacher creativity, student engagement, and learning achievement, provided that it is supported by needs-based planning, structured team organization, collaborative implementation, and reflective as well as continuous supervision. It is expected that this study contributes to the development of adaptive, innovative, and sustainable TPACK-based learning policies and practices in primary schools.